Understanding the Role of User Needs and Perceptions Related to Sub-Seasonal and Seasonal Forecasts on Farmers' Decisions in Kenya: A Systematic Review - Muita, Richard; Dougill, Andrew; Mutemi, Joseph; Aura, Stella; Graham, Richard; Awolala, David; Nkiaka, Elias; Hirons, Linda; Opijah, Franklin (Frontiers in Climate, 2021)
One major challenge facing farmers and other end-users of weather and climate information in Kenya is the linkage between their perceptions, needs and engagements with producers of the information. This is highlighted by increased interest in understanding the constraints on appropriate use of weather and climate information by farmers in decision making. Farmers face extreme weather impacts which constraint the use and choice of the appropriate weather information and other services. The choice between sub-seasonal and seasonal forecasts can enable better decisions by farmers if the forecast information is reliable and integrated through a co-production process.The objective of this study was to analyse the user needs and perceptions of crop farmers, pastoralists and agro-pastoralists in relation to sub-seasonal and seasonal forecasts for 5 counties in Kenya. A total of 200 peer-reviewed and grey literatures were systematically reviewed to understand how the needs and perceptions of users of weather and climate information shaped access and use in decision making. The study also reviewed whether sub-seasonal and seasonal forecasts were adopted and used appropriately.Results show that farmers' perceptions shaped the choice of weather and climate information while sub-seasonal and seasonal forecasts were used for diverse applications. Gender, availability of resources, access and mode of communication were some of the factors influencing use of the information. One lesson learnt was that farmers combined weather and climate information with other coping practices such as agronomic practices and water efficiency management. However, a number of challenges were faced by the users such as insufficient resources, lack of access to information and poor engagement with weather forecasters and extension services.2 This is a provisional file, not the final typeset article This study recommends stakeholder engagements with producers in development of products and services to improve uptake and use of forecasts in decision making.